X-Ray Computed Tomography for Failure Mechanism Characterisation within Layered Pouch Cells: Part I : Lithium-ion battery safety. Issue 1 (3rd January 2023) - Patel, Drasti; Reid, Hamish; Ball, Sarah; Brett, Dan J. L.; Shearing, Paul R.
The assessment of lithium-ion battery (LIB) safety is a multiscale challenge: from the whole-cell architecture to its composite internal three-dimensional (3D) microstructures. Substantial research is required to standardise failure assessments and optimise cell designs to reduce the risks of LIB failure. In this two-part work, the failure response of a 1 Ah layered pouch cell with a commercially available nickel manganese cobalt (NMC) cathode and graphite anode at 100% state of charge (SOC) (4.2 V) is investigated. The mechanisms of two abuse methods: mechanical (by nail penetration) and thermal (by accelerating rate calorimetry) are compared by using a suite of post-mortem analysis methods.